Dedifferentiation of MCF-7 Breast Cancer Continuous Cell Line, Development of Breast Cancer Stem Cells (BCSCs) Enriched Culture and Biomarker Analysis - Ami Ashariati Prayogo; Andi Yasmin Wijaya; Winona May Hendrata; Steven Sheng Looi; Reny I’tishom; Lukman Hakim; Fedik Abdul Rantam; I Ketut Sudiana; Abdurachman Abdurachman (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Cancer stem cells (CSCs) eradication might serve as a robust approach for cancer eradication. MCF-7 as breast cancer continuous cell line is known to contain breast CSCs (BCSCs) for its capability to maintain its original tumor population. CSCs enriched culture is a fundamental tool for CSCs targeted therapy development. Effective and unsophisticated CSCs dedifferentiation protocol for producing CSCs enriched culture is needed.METHODS: MCF-7 cells were cultured initially in Dulbecco's Modified Eagle Medium (DMEM) low glucose medium then changed to DMEM:F12. Serum starvation was performed during each medium refreshment gradually with fetal bovine serum (FBS) concentration of 10%, 5%, 2.5% until reaching 1% FBS concentration. Stable MCF-7 culture was then adapted to serum free culture system, containing DMEM:F12, epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and B27 supplement as dedifferentiation protocol for 18 days. Cluster of differentiation (CD)44 and CD24 double staining immunocytochemistry was performed to evaluate cell stemness.RESULTS: The population of cells expressing BCSCs markers (CD44+/CD24low) in non-adherent single cells subpopulation was significantly increased after the dedifferentiation procedure (70.39%) compared to control groups (0.71%) (p<0.05). In contrast, the expression of BCSCs marker in adherent single cells subpopulation and for both adherent and non-adherent mammosphere the BCSCs markers showed a stable expression.CONCLUSION: BCSCs enrichment of breast cancer cell cultures from MCF-7 breast cancer cell line can be performed. Breast cancer cell plasticity is observed during the dedifferentiation protocol. Development of dedifferentiation inducing protocols can serve as an important foundation for breast cancer therapy development through BCSCs elimination.KEYWORDS: breast neoplasms, cell line, dedifferentiation, immunohistochemistry, neoplastic stem cells